IMPLEMENTASI MANAJEMEN RISIKO PEMBIAYAAN TERHADAP NASABAH MACET PADA BANK SYARIAH INDONESIA KCP SYIAH UTAMA 2 ACEH - Junaidi; Nisa; Muslim; Nurazizah, Nisa (Jurnal Syariah dan Ekonomi Islam, 2023)
This research was conducted to determine the factors of the occurrence of problem financing and the application of risk management in an effort to prevent the occurrence of problem financing at PT. Bank Syariah Indonesia KCP Syiah Utama 2. This study uses a qualitative research method with a descriptive approach. Data collection techniques used are interviews and documentation. The results of the research show that the factors of problematic financing consist of internal factors and external factors. The application of risk management used is risk identification, risk measurement, risk monitoring and risk control. The four risk management processes above include 5C analysis, document completion, and routine monitoring by conducting daily visits. In solving problem financing PT. Bank Syariah Indonesia KCP Syiah Utama 2 uses a persuasive approach by holding deliberations which are then applied to rescheduling, reconditioning, restructuring, and execution of guarantees. The application of risk management used has been running effectively in minimizing the risk of non-performing financing. This is evidenced by an increase in Non Performing Financing (NPF).